Dental rapid heating phosphate investment material for resin patterns
Patent Information
- Application Number
- JP2020184945
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-11-05
Smart Images

Figure 0007630874000008 
Figure 0007630874000009 
Figure 0007630874000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a rapid heating type phosphate-based investment material for use in the dental field that is compatible with resin patterns. [Background technology]
[0002] When indirectly producing metal prosthetic devices for dental prosthetic repair, a method called the lost wax method has been mainly used, which can be explained as follows. A model is made by taking a mold of the dental defect using a mold material called an impression material, and then injecting a model material such as gypsum into the mold to reproduce the shape of the patient's defect outside the mouth. Next, a wax pattern is made on this model to reproduce the shape of the shape to be restored using wax. A refractory investment material is poured around the obtained wax pattern and hardened to form a mold. The mold is then heated to burn out the wax pattern, and molten metal is poured into the space of the mold that has been formed. After further cooling, the mold is broken and the cast is removed to obtain the desired metal prosthetic device. This lost wax method is generally used to produce dental gold alloys, gold-silver-palladium alloys, and alloys for porcelain baking. The composition of this phosphate-based investment material is composed of magnesium oxide and primary ammonium phosphate as binders in the powder material, silica, alumina, zirconium silicate, etc. as refractory materials (aggregates), and a liquid material containing colloidal silica in the special liquid. A mold can be made by mixing and hardening them. By adjusting the concentration of the aqueous solution containing colloidal silica in the special liquid, it is possible to obtain a total expansion (total value of hardening expansion and thermal expansion) that matches the casting shrinkage of various metals. Therefore, this investment material can be used for a wide range of materials, from precious alloys mainly made of gold to non-precious alloys mainly made of nickel and cobalt.
[0003] The aqueous solution containing colloidal silica, which is the liquid material of the phosphate-based investment material, is mixed with the powder material and hardened. During this process, the value of hardening expansion changes depending on the particle size and concentration of the colloidal silica. Furthermore, when the investment material is used in the lost wax method, it is heated to 800-1000°C, so thermal expansion also occurs. The sum of this hardening expansion and thermal expansion compensates for the solidification contraction and thermal contraction of the metal, and adjusts the fit of the prosthetic device.
[0004] On the other hand, aqueous solutions containing colloidal silica used as liquid materials for phosphate-based investment materials are generally alkaline, with a pH of 8.0 to 11.0. The hardening time of the investment material can also be adjusted by changing the pH. This colloidal silica is made of amorphous SiO2, and the average particle size is generally 4 to 100 nm.
[0005] In recent years, digital technology using 3D printers has made remarkable progress, and new technologies have been applied in the field of dentistry, and various digital systems for dental laboratories have been developed to improve the efficiency of dental laboratories. There are several known 3D printers, including stereolithography, inkjet, binder jet, and fused deposition modeling. In casting, a resin pattern made by a 3D printer is used instead of a wax pattern. As with the wax pattern, a refractory investment material is poured around the resin pattern and hardened to form a mold. The mold is then heated to burn out the resin pattern, and casting is performed to obtain a metal prosthetic device.
[0006] In dentistry, the 3D printer methods used for resin patterns are the stereolithography method and the inkjet method. The stereolithography method is a method in which a liquid photocurable resin composition filled in an ink tray is irradiated with light (ultraviolet rays, etc.) to gradually harden the resin, thereby creating a resin pattern of the desired shape. The stereolithography method includes the stereolithography (SLA) method and the digital light processing (DLP) method. On the other hand, the inkjet method is a method in which a liquid photocurable resin is sprayed from the tip of a nozzle, and the resin is irradiated with light (ultraviolet rays, etc.) to gradually harden the resin, thereby creating a resin pattern of the desired shape.
[0007] In recent years, in order to shorten the work time, the heating method for incinerating patterns has changed from "normal heating" in which the temperature of an electric furnace is gradually raised from room temperature to the desired temperature to "rapid heating" in which the pattern is suddenly put into a furnace at the desired temperature. Therefore, the investment material is required not to explode or crack when rapidly heated. However, unlike wax patterns, resin patterns are made of resin, so they expand rapidly when incinerated, and then turn into gas and are incinerated. For this reason, if a resin pattern is used in rapid heating, the investment material may explode and be unable to be cast, or the cracks that occur may cause burrs (fin-like objects that appear partially or entirely around the periphery of the casting) to appear on the casting.
[0008] Patent Document 1 discloses a technology for a rapid heating phosphate-based investment material for pressing. Specifically, the technology discloses a technology for smoothing the surface properties of pressed ceramics such as lithium disilicate by specifying the weight ratio of the powder material of the phosphate-based investment material and using an aqueous solution containing cation-treated colloidal silica as the liquid material. However, although this technology makes the surface properties of pressed ceramics smooth when a wax pattern is used, it does not mention whether it is effective in improving the surface properties of cast bodies or suppressing burrs when a resin pattern is used. Patent Document 2 discloses a technology of a rapid heating type gypsum-based investment material for casting compatible with resin patterns. Specifically, the technology discloses a technology of making the surface quality of the casting smooth and suppressing burrs by including a refractory material with a low thermal expansion coefficient selected from zirconium silicate and alumina. However, even this technology is insufficient in suppressing the surface quality of the casting and the generation of burrs. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2018-193320 A [Patent Document 2] Patent No. 6082388 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention aims to provide a phosphate-based investment material that can be used for metal casting, which has a smooth surface and suppresses burrs when cast using a resin pattern and rapid heating. [Means for solving the problem]
[0011] As a result of extensive research into these problems, the present inventors have arrived at the present invention. That is, the present invention provides: The powder material contains (a) 5-20 wt% magnesium oxide and (b) 8-25 wt% ammonium phosphate, The liquid material is a rapid-heating phosphate-based dental investment material compatible with resin patterns, characterized in that it contains (c) an aqueous solution containing colloidal silica that has been cationically treated with an alumina compound.
[0012] The rapid-heating type dental phosphate-based investing material of the present invention contains at least one of zirconium silicate, zirconia, mullite, alumina, and amorphous silica in the powder material. In the dental rapid-heating phosphate-based investing material of the present invention, (c) the content of alkali metals (content of alkali metal oxides) in an aqueous solution containing colloidal silica cationically treated with an alumina compound is 0.001 to 0.30 wt % or less. In the dental rapid-heating type phosphate-based investing material of the present invention, (c) the aqueous solution containing colloidal silica cationically treated with an alumina compound has a pH of 8.0 to 11.0. The resin pattern used in the dental rapid heating type phosphate-based investment material of the present invention is created by a stereolithography or inkjet 3D printer. Effect of the Invention
[0013] The effects of the present invention are that explosion or cracking of the investment material does not occur, the surface properties of the casting are smooth, and burrs can be suppressed, not only when a conventional wax pattern is used, but also when a resin pattern, which has a different disappearance temperature and disappearance behavior from a wax pattern, is used and incinerated by rapid heating. [Brief description of the drawings]
[0014] [Figure 1] Photograph of the casting in Example 1 [Diagram 2] Photograph of the casting in Comparative Example 7 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The dental rapid heating type phosphate-based investment material according to the present invention will be specifically described below. Note that the present invention is not particularly limited to the following examples. The rapid-heating type dental phosphate-based investing material of the present invention is composed of a powder material and a liquid material. The powder material includes (a) magnesium oxide and (b) monoammonium phosphate. The type of magnesium oxide (a) contained in the powder material is not particularly limited, but it is preferable that the magnesium oxide has a high purity and is finely divided. (a) The average particle size of magnesium oxide is not particularly limited, but the average particle size is preferably 15 to 40 μm, and more preferably 20 to 30 μm. In addition, in the particle size distribution of magnesium oxide, particles of 100 μm or more are preferably within 1 wt %, and more preferably no particles of 100 μm or more are included. Furthermore, particles having a plurality of average particle sizes may be combined. When particles having a plurality of average particle sizes are combined, the average particle size after combination is preferably 15 to 40 μm. In order to obtain the effect of the present invention in the phosphate-based investment material of the present invention, the amount of magnesium oxide must be in the range of 5-20wt% with respect to the powder material of the phosphate-based investment material. If it is less than 5wt%, the strength of the mold is not sufficient, and it becomes insufficient as a mold material, and if it exceeds 20wt%, the amount of aggregate is small, and it may happen that sufficient thermal expansion is not obtained. The thermal expansion of the investment material is preferably 0.5% or more.
[0016] Next, (b) ammonium phosphate dibasic contained in the powder material constituting the dental rapid-heating type phosphate-based investment material of the present invention is not particularly limited as long as it is soluble, and any average particle size or shape can be used without any problems. However, it is preferable that the maximum particle size of ammonium phosphate is small so that it acts as a binder in the investment material. In order to maintain the smoothness of the surface of the cast metal, it is preferable that there are no particles with a particle size of 60 μm or more, and more preferably, of the particles with a particle size of 60 μm or less, the particles with a particle size of 25 μm or less are 10 to 45 wt%, and even more preferably, 20 to 35 wt%. In order to obtain the effects of the present invention in the dental rapid heating phosphate investment material of the present invention, the amount of ammonium phosphate must be in the range of 8-25wt% based on the powder of the phosphate investment material. If the amount is less than 8wt%, the mold strength is not sufficient and the material is insufficient as a mold material, and if it exceeds 25wt%, the surface quality of the casting may become rough and the thermal expansion may not be sufficient. The thermal expansion of the investment material is preferably 0.5% or more.
[0017] Next, the blending ratio of (a) magnesium oxide and (b) ammonium phosphate monobasic contained in the powder material constituting the dental rapid-heating type phosphate-based investment material of the present invention is preferably (a) / (b)=0.3 to 0.8 by weight, and more preferably (a) / (b)=0.4 to 0.6.
[0018] Next, the powder material constituting the dental rapid heating type phosphate-based investment material of the present invention includes a refractory material. As the refractory material, any refractory material used in dental casting investment materials can be used without any restrictions. Specific examples of such materials include quartz, cristobalite, zirconium silicate, zirconia, mullite, alumina, amorphous silica, calcia, yttria, etc. In the present invention, in addition to quartz and cristobalite, it is preferable to include at least one of zirconium silicate, zirconia, mullite, alumina, and amorphous silica, which have a low thermal expansion coefficient. In order to adjust the fluidity of the investment material, aggregates with an average particle size of 5 to 300 μm can be used in combination.
[0019] The amount of these refractory materials to be blended in the dental rapid heating phosphate-based investment material of the present invention to achieve the effects of the present invention is not particularly limited, but the amount of zirconium silicate, zirconia, mullite, alumina, and amorphous silica, which are refractory materials with low thermal expansion coefficients, is preferably 5 to 25 wt%. If the amount is less than 5 wt%, the investment material may crack, and if it exceeds 25 wt%, sufficient thermal expansion may not be obtained. The thermal expansion of the investment material is preferably 0.5% or more.
[0020] Next, the aqueous solution containing colloidal silica cationically treated with an alumina compound (c) contained in the liquid constituting the dental rapid heating type phosphate investment material of the present invention will be described. The cation treatment is roughly divided into a method of treating with a metal element having cationicity and a method of treating with a silane coupling agent having cationicity. In order to achieve the effects of the present invention, it is essential that the surface of the colloidal silica is cationically treated with an alumina compound. In addition to colloidal silica, a water-soluble metal salt may be contained. For example, sodium chloride may be mentioned. First of all, there are two main methods for producing colloidal silica itself. The most common are the water glass method and the alkoxide method. The water glass method involves ion-exchanging sodium silicate to prepare active silicic acid, which is then heated and its pH adjusted with an alkali metal compound.
[0021] The alkoxide method is a so-called Stoeber method, in which silica particles are produced by hydrolyzing alkyl silicate (tetraalkoxysilane) in the presence of a basic catalyst and simultaneously carrying out condensation and particle growth. This method makes it possible to prepare colloidal particles ranging from nanoscale to micronscale. For example, methyl silicate (tetramethoxysilane) or a mixture of methyl silicate and methanol is dropped into a mixed solvent of water, methanol, and ammonia or ammonia and an ammonium salt for 10 to 40 minutes under stirring, and the methyl silicate is reacted with water to produce colloidal silica having a minor axis of 10 to 200 nm and a major axis / minor axis ratio of 1.4 to 2.2.
[0022] First, the method of cationic treatment with an alumina compound will be described. In this method, when colloidal silica is produced by the water glass method, an alumina compound is mixed in advance, sodium silicate is ion-exchanged to prepare active silicic acid, and the pH is adjusted with an alkali metal compound under heating. Specifically, colloidal silica whose surface is coated with an alumina compound can be used. The method of coating is not particularly limited, but a method of mixing and reacting in an aqueous solution is used, and the alumina compound is added to an aqueous colloidal silica solution, which is heated and stirred to obtain the product. As the alumina compound, specifically, sodium aluminate, potassium aluminate, etc. can be preferably used. It is preferable to add an alkali metal compound to adjust the pH to 8.0 to 11.0. As the alkali metal compound, sodium hydroxide and potassium hydroxide can be suitably used. The solid content of the cationic colloidal silica treated with a metal element is preferably 15 to 40 wt%, and more preferably 20 to 30 wt%. The primary particle size of the colloidal silica is not particularly limited, but is preferably 5 to 30 nm, and more preferably 8 to 20 nm.
[0023] Another method for cationic treatment of colloidal silica is to prepare cationic colloidal silica from colloidal silica using a silane coupling agent. In this method, an aqueous solution containing colloidal silica is prepared in advance by a water glass method or an alkoxide method, and then the surface is treated with a silane coupling agent. There is no problem in using an aqueous solution containing colloidal silica that is commercially available. The aqueous solution containing colloidal silica suitable for the present invention has a solid content concentration of preferably 15 to 40 wt%, particularly preferably 20 to 30 wt%. The primary particle size of this colloidal silica is not particularly limited, but is preferably 5 to 30 nm, particularly preferably 8 to 20 nm. As a method for producing an aqueous solution containing cationic colloidal silica with a silane coupling agent, there is a method in which a treating amount of the silane coupling agent is added to an aqueous colloidal silica solution and stirred to treat the colloidal silica. For example, the desired treatment solution can be obtained by heating to a range of 50 to 80°C and stirring for about 1 to 2 hours. The weight ratio of the aqueous colloidal silica solution to the silane coupling agent is preferably 50:1 to 5:1.
[0024] Specific examples of silane coupling agents having this cationic property include N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-triethoxysilyl-N-(α,γ-dimethyl-butylidene)propylamine, N-phenyl-γ-aminopropyltrimethoxysilane, N-(vinylbenzyl)-β-aminoethyl-γ-aminopropyltriethoxysilane hydrochloride, octadecyldimethyl-(γ-trimethoxysilylpropyl)-ammonium chloride, and the like. Among these, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, and γ-aminopropyltrimethoxysilane are preferably used because of their good reactivity with colloidal silica. These silane coupling agents may be used alone or in combination of two or more kinds. After carrying out these silane coupling treatments, it is preferable to add an alkali metal compound to adjust the pH to 8.0 to 11.0. As these alkali metal compounds, sodium hydroxide and potassium hydroxide can be suitably used.
[0025] In addition, (c) the aqueous solution containing colloidal silica cationically treated with an alumina compound preferably contains an alkali metal, and the content of the alkali metal (oxide equivalent) is more preferably 0.30 wt% or less, and more preferably 0.001 wt% or more. If the content of alkali metals (converted into oxides) is less than 0.001 wt%, the hardening time of the investment material may become extremely slow, while if the content of alkali metals (converted into oxides) exceeds 0.30 wt%, the surface quality of the casting may become poor. Furthermore, it is preferable that the pH of the aqueous solution containing the colloidal silica cation-treated with the alumina compound (c) is 8.0 to 11.0. If the pH is less than 8.0, the hardening time of the investment material becomes extremely slow. If the pH is more than 11.0, the hardening time of the investment material becomes too fast.
[0026] Next, the mixing ratio of the powder material and the liquid material in the dental phosphate-based investing material of the present invention is preferably 17 to 25 mL of liquid material per 100 g of powder material, more preferably 18 to 22 mL.
[0027] Next, the corresponding resin pattern in the dental phosphate-based investment material of the present invention will be described. The resin pattern is preferably a resin pattern made by a 3D printer of the photolithography method (SLA method, DLP method) or the inkjet method, a photopolymerization type resin pattern, and a room temperature polymerization type resin pattern. Specifically, the resin pattern may be a photocurable or thermosetting resin such as a (meth)acrylate resin, and is preferably one with little polymerization shrinkage.
[0028] Polymerizable acrylic compounds that can be used in the resin pattern composition are not limited, but are selected from compounds containing an unsaturated double bond group that is widely used as a radical polymerizable monomer in the fields of dentistry and the chemical industry and is highly safe to living organisms.
[0029] For example, monomers, oligomers or polymers having one or more unsaturated double bond groups such as methyl acrylate, methyl methacrylate, methacrylic acid, ethyl acrylate, ethyl methacrylate, isopropyl methacrylate, (meth)acryloyl groups, (meth)acrylamide groups and vinyl groups are preferably used.
[0030] The term "(meth)acrylate" refers to both acrylates and methacrylates. For example, in addition to an unsaturated double bond group, compounds having one or more of a hydrocarbon group, a phenyl group, a hydroxyl group, an acid group, an acid amide group, an amino group, a thiol group, a disulfide group, a cyclic group, a heterocyclic group, a halogen group, a silanol group, a pyrrolidone group, a urethane bond, an ester bond, an ether bond, an alkylene glycol group, etc., can be mentioned. Suitable radical polymerizable monomers are (meth)acrylic acid ester derivatives having the above-mentioned functional groups or bonds.
[0031] The radical polymerizable monomer is preferably combined with a crosslinkable monomer and a diluent monomer in order to maintain an appropriate viscosity.
[0032] Crosslinking monomers include urethane (meth)acrylates, including mono-, di-, tri-, and tetra-ethylene glycol di(meth)acrylates.
[0033] "Urethane di-(meth)acrylates" refer to the reaction products of suitable diisocyanates with hydroxyalkyl-mono-(meth)acrylates in a 1:2 molar ratio. "Urethane tri-(meth)acrylates" are the reaction products of suitable diisocyanates with hydroxyalkyl-di-(meth)acrylates and hydroxyalkyl-mono-(meth)acrylates in a 1:1:1 molar ratio. Urethane tetra-(meth)acrylates are the reaction products of suitable diisocyanates with hydroxyalkyl-di-(meth)acrylates in a 1:2 molar ratio.
[0034] Di-[(meth)acryloxyethyl]trimethylhexamethylene diurethane, di-[(meth)acryloxypropyl]trimethylhexamethylene diurethane, di-[(meth)acryloxybutyl]trimethylhexamethylene diurethane, di-[(meth)acryloxypentyl]trimethylhexamethylene diurethane, di-[(meth)acryloxyhexyl]trimethylhexamethylene diurethane, di-[(meth)acryloxydecyl]trimethylhexamethylene diurethane, di-[(meth)acryloxyethyl]isophorone diurethane, di-[(meth)acryloxypropyl]isophorone diurethane , di-[(meth)acryloxybutyl]isophorone diurethane, di-[(meth)acryloxypentyl]isophorone diurethane, di-[(meth)acryloxyhexyl]isophorone diurethane, di-[(meth)acryloxyethyl]hexamethylene diurethane, 2,2 bis[4-(2-hydroxy-3-methacryloyloxypropoxy)phenyl]propane, 2,2 bis[4-(2-methylacryloyloxyethoxy)-phenyl]propane, 2,2 bis[4-methacryloyloxyphenyl]propane, and 2,2 bis[4-(3-methacryloyloxypropoxy)phenyl]propane. Di-[(meth)acryloxyethyl]trimethylhexamethylenediurethane, di-[(meth)acryloxypropyl]trimethylhexamethylenediurethane, di-[(meth)acryloxybutyl]trimethylhexamethylenediurethane, 2,2 bis[4-(2-hydroxy-3-methacryloyloxypropoxy)phenyl]propane, 2,2 bis[4-(2-methylacryloyloxyethoxy)-phenyl]propane are preferred. Two or more of these compounds may be used together if desired.
[0035] Specific examples of preferred diluent monomers include mono-, di-, tri-, and tetra-ethylene glycol di(meth)acrylates, polyethylene glycol (meth)acrylates, 1,4-di[(meth)acryloxy]butylene, 1,6-di[(meth)acryloxy]hexamethylene, neopentyl glycol di(meth)acryloxy]hexamethylene, neopentyl glycol di(meth)acrylate, tetramethylolpropane-tetra(meth)acrylate, methyl(meth)acrylate, (meth)acrylamide, and styrene. Ethylene glycol di(meth)acrylate and triethylene glycol di(meth)acrylate are preferred. Two or more of these compounds may be used together if desired.
[0036] Photopolymerization catalysts and reducing agents that can be used for 3D printer resin patterns and photopolymerized resin patterns include camphorquinone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, or methylbenzoin; and / or reducing agents, such as tertiary amines.
[0037] The absorption wavelength region of the 3D printer resin pattern and the photopolymerized resin pattern can be initiated by irradiating the composition with light energy having a wavelength preferably in the range of about 300 to 600 nm. Photoinitiators selected from the class of acylphosphine oxides can also be used. These compounds include, for example, monoacylphosphine oxide derivatives, bisacylphosphine oxide derivatives, and triacylphosphine derivatives.
[0038] Thermal polymerization initiators that can be used in room temperature polymerization resin patterns include organic peroxides such as benzoyl peroxide, parachlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, acetyl peroxide, lauroyl peroxide, tertiary butyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane, 2,5-dihydroperoxide, methyl ethyl ketone peroxide, and tertiary butyl peroxybenzoate, and azo compounds such as azobisisobutyronitrile, methyl azobisisobutyrate, and azobiscyanovaleric acid. Among these, it is preferable to select and use from benzoyl peroxide, azobisisobutyronitrile, trimethylbarbituric acid, and tributylborane oxide in the present invention. The present invention will be described in more detail and specifically below with reference to examples, but the present invention is not limited thereto. EXAMPLES
[0039] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The particle size of magnesium oxide was measured using a Nikkiso Microtrack HRA model, and ammonium phosphate dibasic was sieved using a JIS standard sieve.
[0040] (Preparation of Magnesium Oxide) The magnesium oxide raw material was crushed and classified to prepare a powder with an average particle size of 25 μm and a ratio of particles of 100 μm or more within 1 wt %. (Preparation of Ammonium Monophosphate) Ammonium monophosphate was pulverized and then passed through a 250 mesh (60 μm) sieve, so that the particles that passed through a 25 μm (500 mesh) sieve accounted for 30 wt % of the powder. (Fireproof material) The refractory materials used were cristobalite (200 mesh (77 μm) full), quartz (200 mesh (77 μm) full), zirconium silicate (200 mesh (77 μm) full), and zirconia (200 mesh (77 μm) full). The powder materials were mixed for 30 minutes using a ball mill with the compositions shown in the following table. They were then sieved through a 1000 μm sieve to obtain powder materials.
[0041] (Preparation of liquid material A) A colloidal silica aqueous solution was prepared by adding sodium aluminate to a commercially available aqueous sodium silicate solution as the raw material and heating it. The molar ratio of Al2O3 / SiO2 was adjusted to 0.001. The silica particle size was controlled during the ion exchange concentration process, and the primary particle size was adjusted to 10 nm, the solid content concentration to 30 wt%, and the pH to 9.5 using sodium hydroxide. The alkali metal content (oxide equivalent) was 0.15 wt%. (Preparation of liquid material B) The same alumina treatment as in Liquid A was carried out using the colloidal silica in Liquid A, and the pH was adjusted to 7.0 using sodium hydroxide. The amount of alkali metal (oxide equivalent) was 0.02 wt%. (Preparation of liquid material C) The same alumina treatment as in Liquid Material A was carried out using the colloidal silica in Liquid Material A, and the pH was adjusted to 12.0 using sodium hydroxide. The amount of alkali metal (oxide equivalent) was 0.80 wt%. (Preparation of liquid material D) The same alumina treatment as in Liquid A was carried out using the colloidal silica in Liquid A, and the pH was adjusted to 8.0 using sodium hydroxide. The amount of alkali metal (oxide equivalent) was 0.01 wt%. (Preparation of liquid material E) The same alumina treatment as in Liquid A was carried out using the colloidal silica in Liquid A, and the pH was adjusted to 11.0 using sodium hydroxide. The amount of alkali metal (oxide equivalent) was 0.30 wt%. (Adjustment of liquid material F) N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KBM-603, manufactured by Shin-Etsu Chemical Co., Ltd.) was added in a mass ratio of 10:1 to acidic colloidal silica (solid content concentration 30 wt%) with a primary particle size of 10 nm, heated to a temperature of 80°C, stirred, and then adjusted to pH 9.5 using 1N sodium hydroxide. The alkali metal content (oxide equivalent) was 0.15 wt%. (Preparation of liquid material G) The same treatment as for liquid material F was carried out, and the liquid material was adjusted to have a pH of 7.0 to give liquid material G. The content of alkali metals (converted into oxide) was 0.01 wt%. (Preparation of liquid material H) The same treatment as for liquid material F was carried out, and a liquid material was adjusted to have a pH of 12.0, to give liquid material H. The content of alkali metals (converted into oxide) was 0.80 wt%. (Preparation of Liquid Material I) The same treatment as for liquid material F was carried out to prepare a liquid material having a pH of 8.0, which was named liquid material I. The content of alkali metals (converted into oxide) was 0.01 wt%. (Preparation of liquid material J) The same treatment as for liquid material F was carried out, and the liquid material was adjusted to have a pH of 11.0, to give liquid material J. The content of alkali metals (converted into oxide) was 0.30 wt%. (Preparation of liquid material K) A colloidal silica aqueous solution was prepared by adding potassium aluminate to a commercially available aqueous sodium silicate solution as the raw material and heating it. The molar ratio of Al2O3 / SiO2 was adjusted to 0.001. The silica particle size was controlled during the ion exchange concentration process, and the primary particle size was adjusted to 10 nm, the solid content concentration to 30 wt%, and the pH to 9.5 using sodium hydroxide. The alkali metal content (oxide equivalent) was 0.15 wt%. (Preparation of liquid material L (aqueous colloidal silica solution of comparative example)) As a comparative example, a solution containing non-cation-treated colloidal silica, SI-30 (manufactured by JGC Catalysts), was used. The primary particle size was 11 nm and the solid content was 30 wt%. This was designated as liquid material K. (Measurement of curing time and dimensional change due to heat (thermal expansion)) The investment materials were prepared using the powder and liquid materials in the following Examples and Comparative Examples composition tables, and tests were performed on the hardening time and dimensional change (thermal expansion) due to heat up to 700°C in accordance with the standard JIS T 6612:2013 (investment materials for high-temperature dental casting and refractory materials for ceramics). (3D printer device) For the stereolithography method, we used the DLP D30 (Rapidshape) and the SLA DIGITAL WAX 020D (DWS). For the inkjet method, we used the ProJet MJP 3600 Dental (3D Systems). (3D printer materials) We used Cast (Nextdent) for DLP and RF080 RESIN (DWS) for SLA, as well as VisiJet M3 Dentcast (3D Systems) for inkjet. (Measurement of thermal expansion coefficient of 3D printer materials) A cylindrical resin pattern of φ5mm x 21mm was printed using DLP and SLA 3D printers. After printing, the support was removed by ultrasonic cleaning in isopropanol for 5 minutes. Then, the pattern was post-cured for 15 minutes using an LC-3DPrint Box (Nextdent). A cylindrical resin pattern of φ5mm × 21mm was printed using an inkjet 3D printer. After printing, the pattern was ultrasonically cleaned in 50℃ water for 10 minutes to remove the supports. The specimens were adjusted to φ4 mm × 20 mm using a rotary polisher. The specimens were measured (RIGAKU: TMA 8310) from 25°C to 100°C at a heating rate of 2°C / min. The maximum value during the measurement from 25°C to 100°C was calculated, and the average value was used as the thermal expansion coefficient (n=2). (Preparation of test specimens for evaluation of burrs and surface properties) A 10mm x 10mm x 2mm resin pattern plate was printed using DLP and SLA 3D printers. After printing, the plate was ultrasonically cleaned in isopropanol for 5 minutes to remove the supports. Then, the plate was post-cured for 15 minutes using an LC-3Dprint Box (Nextdent). A resin pattern plate measuring 10 mm x 10 mm x 2 mm was printed using an inkjet 3D printer. After printing, the plate was ultrasonically cleaned in water at 50°C for 10 minutes to remove the supports. The wax pattern plate in the comparative example was prepared by adjusting paraffin wax (manufactured by Matsukaze) to 10 mm×10 mm×2 mm. The prepared resin pattern plate was planted on a casting rubber stand. The phosphate-based investment material prepared using the powder and liquid materials in the following Example and Comparative Example Composition Tables was mixed for 60 seconds in a lab mixer (Matsukaze) and poured into a casting ring. 40 minutes after embedding, it was placed in an incinerator at 900°C and held for 1 hour. Then, casting was performed using Cobaltan (Matsukaze), a cobalt-chromium alloy for dental casting. After casting, the cast was dug out and evaluated for the presence or absence of burrs and surface properties. (Evaluation of the presence or absence of burrs) The presence or absence of burrs was evaluated visually using the following 5-point scale: No burrs at all (◎), some burrs (○), and burrs that are not a problem (●) are clinically acceptable. ◎: No burrs at all ○: Some burrs ●: There are burrs but it is not a problem △: Somewhat burred ×: Many burrs (Evaluation of surface properties) The surface properties were evaluated by measuring the surface roughness (Ra: arithmetic mean roughness) of the castings using a stylus-type surface roughness measuring instrument, Surfcom 1500SD (Tokyo Seimitsu Co., Ltd.). Measurements were performed three times for each sample, and the average value was used. A surface roughness of 25 μm or less is clinically acceptable, with 10 μm or less being optimal. The surface roughness of the resin pattern plate and wax pattern plate was 1 μm.
[0042] [Table 1]
[0043] [Table 2]
[0044] [Table 3]
[0045] [Table 4]
[0046] [Table 5]
[0047] [Table 6]
[0048] [Table 7]
[0049] (Consideration) In Examples 1 to 15, the results were that there was no burr (◎), there was some burr (◯), or there was burr but no problem (●), and the surface roughness (Ra) was 25 μm or less, so that it was clinically acceptable. In Example 10, the dimensional change due to heat (thermal expansion) was low at 0.5%, so if a metal prosthetic device was made, a clinically satisfactory fit may not be obtained. From Examples 1, 2, and 11 to 13, it can be used regardless of the type of pattern. On the other hand, in Comparative Examples 1 to 6, which were subjected to cationic treatment using a silane coupling agent, there was some burr (△), which resulted in clinical problems. In addition, although the surface roughness was 25 μm or less, it was larger than that of the aqueous solution containing colloidal silica cationic treated with an alumina compound. In Comparative Examples 7 to 9 and 12, there was some burr (△) or many burrs (×), and the surface roughness was also 25 μm or more, which resulted in clinical problems. In Comparative Examples 10 and 11, the investment material exploded during incineration, making casting impossible. (effect) From the above results, it is apparent that the present invention provides a phosphate-based investment material that is less likely to produce burrs when casting using a resin pattern and that can produce castings with smooth surface properties.
Claims
1. The powder material contains (a) 5-20 wt% magnesium oxide and (b) 8-25 wt% ammonium phosphate, A dental rapid-heating phosphate-based investment material compatible with resin patterns, characterized in that the liquid material contains (c) an aqueous solution containing colloidal silica whose surface has been cationically treated with an alumina compound.
2. The powder material contains (a) 5-20 wt% magnesium oxide and (b) 8-25 wt% ammonium phosphate, A dental rapid-heating phosphate-based investing material compatible with resin patterns, characterized in that the liquid material contains (c) an aqueous solution containing colloidal silica surface-treated with a cationic silane coupling material.
3. 3. The dental rapid heating type phosphate-based investing material according to claim 1, wherein the powder material contains at least one of zirconium silicate, zirconia, mullite, alumina, and amorphous silica.
4. The dental rapid heating type phosphate-based investment material according to claim 1, characterized in that the content of alkali metal (converted into oxide) in the aqueous solution containing colloidal silica containing the alumina compound (c) is 0.001 to 0.30 wt %.
5. 3. The dental rapid-heating phosphate-based investing material according to claim 1, characterized in that the aqueous solution containing colloidal silica (c) has a pH of 8.0 to 11.
0.
6. The dental rapid-heating phosphate-based investment material according to claim 1 or 2, characterized in that the resin pattern is created by a 3D printer using a photopolymerization method or an inkjet method.
Citation Information
Patent Citations
Thermal transfer paper
JP1985082388A
Non-silica molding material for titanium casting product for dentistry
JP1991189045A
Manufacturing process of chemically bonded sol-gel ceramics
JP2003508627A
Dental phosphate-based buried material
JP2018193320A